2020
DOI: 10.1017/s0021859620001045
|View full text |Cite
|
Sign up to set email alerts
|

How will future climate depending agronomic management impact the yield risk of wheat cropping systems? A regional case study of Eastern Denmark

Abstract: One of the major challenges in agriculture is how climate change influences crop production, for different environmental (soil type, topography, groundwater depth, etc.) and agronomic management conditions. Through systems modelling, this study aims to quantify the impact of future climate on yield risk of winter wheat for two common soil types of Eastern Denmark. The agro-ecosystem model DAISY was used to simulate arable, conventional cropping systems (CSs) and the study focused on the three main management f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…All crops show an increase of yield concomitant with temperatures and CO 2 concentrations increases, although the optimal range of temperatures for increases varies from one crop and locations combination to another. This has been reported in previous studies, as e.g., in Rötter et al (2011), Rötter et al (2013, Ozturk et al (2018), Macholdt et al (2021), Palosuo et al (2021). All these studies emphasize that crops in the Nordic countries can benefit from increased temperatures until a certain threshold, depending on the crop, location and model considered.…”
Section: Production and Risks Of Failure Predicted Trendssupporting
confidence: 80%
See 1 more Smart Citation
“…All crops show an increase of yield concomitant with temperatures and CO 2 concentrations increases, although the optimal range of temperatures for increases varies from one crop and locations combination to another. This has been reported in previous studies, as e.g., in Rötter et al (2011), Rötter et al (2013, Ozturk et al (2018), Macholdt et al (2021), Palosuo et al (2021). All these studies emphasize that crops in the Nordic countries can benefit from increased temperatures until a certain threshold, depending on the crop, location and model considered.…”
Section: Production and Risks Of Failure Predicted Trendssupporting
confidence: 80%
“…Their results suggest that the likeliness of reaching an appropriate fodder quality would increase for most regions in Sweden, with some exceptions due to the effects of water stress, and that yield should not significantly increase under future climate conditions. More recently, Macholdt et al (2021) used the DAISY crop model to simulate the impact of future climate on yield risk of winter wheat in eastern Denmark. There results showed that adapted nitrogen supply and soil organic contents could mitigate the effects of climate change on the yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, temperature increases associated with climate change could contribute to losses of SOC. enhanced levels of SOC may contribute to less production risk and more stable yields [15], as demonstrated in modelling studies on wheat.…”
Section: Introductionmentioning
confidence: 89%
“…Assessing the stability of varieties is an important issue related to both genetic and agronomic progress in a changing climate [16,17]. It allows for the identification of genotypes or cultivars adapted to specific climatic and soil conditions, as well as production requirements.…”
Section: Discussionmentioning
confidence: 99%